2021
DOI: 10.1002/dad2.12244
|View full text |Cite
|
Sign up to set email alerts
|

Brain atrophy trajectories predict differential functional performance in Alzheimer's disease: Moderations with apolipoprotein E and sex

Abstract: Introduction We examine whether distinct brain atrophy patterns (using brain parenchymal fraction [BPF]) differentially predict functional performance and decline in Alzheimer's disease (AD), and are independently moderated by (1) a key AD genetic risk marker (apolipoprotein E [ APOE ]), (2) sex, and (3) high‐risk group (women APOE ɛ4 carriers). Methods We used a 2‐year longitudinal sample of AD patients (baseline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 62 publications
(103 reference statements)
0
3
1
Order By: Relevance
“…We revealed the effect of disease duration on the integrity of the brain. Pyun et al (2017) noted that women had an increased risk of brain atrophy (Ferretti et al, 2018;Sapkota et al, 2021), but our results showed men had a higher proportion of worse global cerebral frontal atrophy and MTA. This might be because brain atrophy accelerates over time, and many factors such as hypertension, hyperlipidemia, smoking, and drinking result in small vessel disease, which may lead to brain atrophy, while these factors occur mostly in men.…”
Section: Discussioncontrasting
confidence: 64%
“…We revealed the effect of disease duration on the integrity of the brain. Pyun et al (2017) noted that women had an increased risk of brain atrophy (Ferretti et al, 2018;Sapkota et al, 2021), but our results showed men had a higher proportion of worse global cerebral frontal atrophy and MTA. This might be because brain atrophy accelerates over time, and many factors such as hypertension, hyperlipidemia, smoking, and drinking result in small vessel disease, which may lead to brain atrophy, while these factors occur mostly in men.…”
Section: Discussioncontrasting
confidence: 64%
“…In the worst prognosis group, there were almost twice as many female than male APOE ε4 carriers, suggesting that the ε4 allele has a disproportionately detrimental effect in women. Women had a greater association between whole brain atrophy and functional decline than men, and female ε4 carriers had the greatest functional decline for a given level of whole brain atrophy 290 . The interaction between sex and APOE influences the accumulation of AD pathology.…”
Section: Adni's Contributions To Understanding Ad Disease Progressionmentioning
confidence: 95%
“…Women had a greater association between whole brain atrophy and functional decline than men, and female ε4 carriers had the greatest functional decline for a given level of whole brain atrophy. 290 The interaction between sex and APOE influences the accumulation of AD pathology. Female ε4 carriers had a faster accumulation of Aβ in the striatum, followed by accumulation of tau in limbic regions than male ε4 carriers or female ε4 non‐carriers.…”
Section: Adni's Contributions To Understanding Ad Disease Progressionmentioning
confidence: 99%
“…When examining combined APOE4 and WMH effects, prior studies have demonstrated worse attention/executive function in APOE4 carriers with dementia [ 22 ]. Additionally, APOE4 status was a key moderator in the relationship between brain atrophy and functional impairment in the dementia stage [ 23 ]. However, it remains to be known if APOE4 is a key effect modifier in the relationship between WMH and GMV, especially early in the disease course.…”
Section: Introductionmentioning
confidence: 99%